Taxonomic and faunistic comments on European Parydra Stenhammar, 1844 (Diptera: Ephydridae) with new species from Finland and Jordan - Stuke, Jens-Hermann (Zootaxa, 2025)
Parydra hautalai spec. nov. (Finland), Parydra kahanpaai spec. nov. (Finland) and Parydra cryptica spec. nov. (Jordan) are described. Four new synonyms are proposed: Parydra stagnicola (Robineau-Desvoidy, 1830) = Parydra coarctata (Fallén, 1813) (syn. nov.), Parydra danensis Stuke 2012 = Parydra flavitarsis (Dahl, 1964) (syn. nov.) and Parydra ralloi Canzoneri & Meneghini 1978 = Parydra albifacies (Duda 1942) = Parydra hecate (Haliday, 1833) (syn. nov.). A new subgenus position is proposed for Parydra (Chaetoapnaea) flavitarsis (Dahl, 1964), Parydra (Chaetoapnaea) nubecula Becker, 1896, Parydra (Chaetoapnaea) quinquemaculata Becker, 1896 and Parydra (Chaetoapnaea) undulata Becker, 1896. Parydra unicolor (Becker, 1926) is treated as a nomen dubium. A lectotype is designated for Parydra nigritarsis Strobl, 1893. Parydra articulata Canzoneri & Meneghini is reported from Europe for the first time. New faunistic country records are listed from Croatia, Cyprus, France, Georgia, Greece, Jordan, Kyrgyzstan, Morocco and Portugal (Madeira). A key to European Parydra species is presented. Illustrations are provided of the habitus and male terminalia for most European Parydra species. All European Parydra species are listed with their synonyms. A short diagnosis and summaries of the European distribution and known biology are also presented for all European Parydra species.